2012
DOI: 10.1177/0194599812450256
|View full text |Cite
|
Sign up to set email alerts
|

All‐Cause Mortality and Obstructive Sleep Apnea Severity Revisited

Abstract: Increasing OSAS severity, measured by a validated home sleep test and quantified by AHI, the apnea index, and the desaturation index, is independently associated with modestly increased all-cause mortality in patients younger than 50 years after adjustment for major confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…OSA subjects had a higher mortality rate than subjects of the same age in the general population [27], [28], and appeared to have more excess mortality in patients younger than 50 years of age [28], [29].In the Sleep Heart Health Study, OSA was not associated with increased mortality in subjects over 70 years of age [11]. Another recently published study further demonstrated that OSA was not associated with mortality in persons >75 years old [14].OSA in the elderly may not be associated with the same increase in mortality than in middle-aged patients [30].In the current meta-analysis, the age of subjects in the included studies varied in these studies, and it might influence the findings of the meta-analysis.…”
Section: Discussionmentioning
confidence: 96%
“…OSA subjects had a higher mortality rate than subjects of the same age in the general population [27], [28], and appeared to have more excess mortality in patients younger than 50 years of age [28], [29].In the Sleep Heart Health Study, OSA was not associated with increased mortality in subjects over 70 years of age [11]. Another recently published study further demonstrated that OSA was not associated with mortality in persons >75 years old [14].OSA in the elderly may not be associated with the same increase in mortality than in middle-aged patients [30].In the current meta-analysis, the age of subjects in the included studies varied in these studies, and it might influence the findings of the meta-analysis.…”
Section: Discussionmentioning
confidence: 96%
“…3,[6][7][8][9][10][11] Moreover, OSA also plays a role in cardiovascular and cerebrovascular complications, 9,[12][13][14] and increases the mortality. [15][16][17] However, it is estimated that only 10% of the people with this sleep-disordered breathing are diagnosed and treated. 4,[18][19][20] Polysomnography (PSG) is the gold-standard to diagnose OSA; however, it is time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive apnea events, on the other hand, are extremely rare in healthy young children and recent studies have estimated that obstructive sleep apnea is estimated to affect between 1% and 4% of infants [6]. Whereas the most severe effects of SAHS in adults are linked to hypertension [7], cardiovascular disease [8] and the dangers arising from vehicular accidents due to daytime sleepiness [9], sleep-related breathing disorders in infants and young children have been linked to several negative developmental effects, such as cognitive impairment [10], depression [11], and attention deficit/hyperactivity disorder [12].…”
Section: Introductionmentioning
confidence: 99%